Historical analysis of the economic life-cycle performance of public school buildings. Issue 7 (3rd October 2019) - Salvado, Filipa; de Almeida, Nuno Marques; Azevedo, Álvaro Vale e
ABSTRACT: Scientific community and practitioners of the Architecture, Engineering and Construction (AEC) sector have been developing life-cycle cost (LCC) concept for the past decades. However, information on a building's economic performance throughout its life-cycle is seldom readily available or accurate. This hinders the fulfilment of recommendations of international and regional standards, procurement guidelines and regulations, and for building management (BM) professionals to fully incorporate the LCC concept into their daily practice. This paper seeks to contribute to solving these difficulties by presenting a conceptual framework that enables LCC-informed decisions in BM, together with its empirical application to a portfolio of 158 public school buildings in Portugal (constructed area of 1, 437, 594 m 2 ). It involved the gathering, organization and treatment of historical data of school buildings originally constructed from 1942 onwards. The historical analysis is presented in the form of three types of economic life-cycle key performance indicators (time series, indexes and relative ratios). It originated a database with more than 1.4 million results that offer a profound understanding of historical economic performance of this portfolio. The results can be adapted and used to benchmark or estimate construction, operation, maintenance, repair, replacement, rehabilitation, energy consumption, water consumption and deconstruction costs of buildings throughout the world.